Investigation on Transition Characteristics of a Modified RAE5243 Airfoil - Zhiyong Liu; Hongbiao Wang; Zhao Zhang; Xiang Liu; Fengxue Qian (Energies, 2024)
The transition characteristics of a modified RAE5243 airfoil were investigated using a wind tunnel test and numerical simulations. Transition detection is of great significance for the assessment of drag reduction. In wind tunnel tests, transition location can be detected by infrared thermography. However, in subsonic and transonic wind tunnel tests, the temperature difference between the laminar flow region and turbulent flow region is small. Moreover, the test models are usually made of metals, which make the transition location hard to identify. Combined with infrared thermography, a carbon nanotube heating coating powered by electricity was used to detect the transition location of a modified RAE5243 airfoil wing. The effects of heating power, angle of attack (AOA), and Mach number were studied. The results show that heating power has no impact on transition location. As the AOA increases, the transition location moves forward. With an increase in Mach number, the transition location moves forward first and then backward, and it reaches its most forward point at Ma = 0.75. The results of our numerical simulations indicate that, at Ma<semantics>≥</semantics> 0.75, a shock wave appears on the wing, and the transition is closely related to the shock wave rather than the adverse pressure gradient.